Inquiry Into The Ethnic Superiority Thesis Of The Bell Curve : A Cognitive Comparative Study Of Malay And Chinese In USM - Zulkernain, Mohd Noordinie (2017)
This study is based on the probe into ethnic intelligence superiority thesis by Herrnstein and Murray (1994) in "The Bell Curve" book. The book suggested that certain ethnic groups were superior intellectually than another due to genetics and this is not amenable to intervention. The main purpose of this research is to scientifically examine their nature stance. This research brings the arguments to the Malaysian context, by looking at the Malays and the Chinese, two largest ethnic groups in Penang. During the British colonial period, the Malays were described as lazy and lack intellectual capacity but the Chinese were viewed oppositely as hard working and academically inclined.